Effects of Global Warming in the Existence of Polar Bear: A Modelling Study using Interval Uncertainty Approach - Gayen, Sailen; Panja, Prabir; Jana, Dipak Kumar; Mondal, Subrata (Journal of Applied Nonlinear Dynamics, 2026)
In this article, the interaction dynamics of seals and polar bears have been discussed in the presence of global warming. It is assumed that seals grow logistically in the absence of a polar bear. It is considered that polar bears consume seal through Holling II functional response. It is also assumed that polar bears may grow logistically in the absence of seals and global warming. It is also considered that global warming increases constantly and decreases due to natural decay. Here, most of the model parameters are considered imprecise in nature by taking interval values. Persistence and extinction conditions of seal and polar bears are investigated. The local stability of the model around each equilibrium point is studied. We investigate the model’s global stability around the positive equilibrium point. It is observed that the increase in the value of p may decrease the population of the polar bear. It is found that the increase in global warming may reduce the environmental carrying capacity of the polar bear. It is seen that the density of seals, polar bears, and global warming are highly influenced by the uncertain values of the model parameters. It is found that the seal and polar bear may coexist in the environment in the presence of global warming. The conclusions are supported by the presentation of some numerical simulation results.